(untitled) (Archaeologia Adriatica, 2021)
During the Trajanic era, Ancona was one of the greatest ports of the Western Adriatic. Scholars have so far considered its remains from a limited historical and topographic perspective. This paper explores the Roman port of Ancona during the Imperial period, through a multidisciplinary examination of literary, archaeological and epigraphic sources. This paper investigates the scale, capacity and urban setting of Ancona’s port. Using topographic observations and excavation data, the first section summarises the form and development of the port and identifies its recurring elements, including the quay, mole(s), lighthouse, horrea, etc. The second section investigates the agents and sponsorships responsible for the construction of Ancona’s port. The third section examines the capacity of the port. Using epigraphic, statistical and shipwreck data, it assesses the capacity of the port, by analysing berth widths and the mooring and manoeuvring of ships. The fourth section explores its urban setting and makes a case for the practical and monumental characters of the port. Supporting information on the port topography and epigraphic and archaeological data are presented in the Table.